Expansion of clinical pharmacy through increased use of outpatient pharmacists for anticoagulation services. (1st April 2015) - Philip, Achsah; Green, Monica; Hoffman, Therese; Gautreaux, Stefani; Wallace, David; Roux, Ryan; Garey, Kevin W.
Abstract: Purpose: The expansion of clinical pharmacy services through increased use of outpatient pharmacists for anticoagulation services is described. Summary: Due to the high demand for clinical pharmacist services by patients and medical staff at Harris Health System in Houston, Texas, and the strict budgetary restrictions to improve the quality of care through cost-neutral services, a new telephone anticoagulation monitoring service, provided by clinical pharmacists, was established at four of the busiest anticoagulation ambulatory care centers within the system. One clinical staff pharmacist was trained in each of the four clinics by a clinical pharmacy specialist. Each pharmacist received roughly two weeks of training to provide this service. Implementation of the new anticoagulation monitoring service occurred on April 1, 2013. Data collected between October 2011 and April 2014 revealed significantly more visits per month for the clinical pharmacy service after the implementation of the telephone anticoagulation monitoring service ( p = 0.011). Redistribution of workflow resulted in a 16% increase in clinical pharmacy patient volume at the ambulatory care clinics ( p = 0.011). The percentage of International Normalized Ratio values in the therapeutic range, the proportion of hospitalizations due to thromboembolic or bleeding events, work hours per prescription volume, project completion rates, and the number of students precepted did not significantly differ between groups. Conclusion: The implementation of a clinical pharmacy telephone service for patients receiving anticoagulation at an outpatient center resulted in increased patient clinic visits without adversely affecting patient outcomes or increasing personnel or costs.